The lung microbiome dynamics between stability and exacerbation in chronic obstructive pulmonary disease (COPD): Current perspectives. (October 2019) - Dima, Efrosini; Kyriakoudi, Anna; Kaponi, Maria; Vasileiadis, Ioannis; Stamou, Panagiota; Koutsoukou, Antonia; Koulouris, Nikolaos G.; Rovina, Nikoletta
Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disorder with a course that is not uniform for all COPD patients. Although smoking is considered as the major cause of the disease, persistent or recurrent infections seem to play a particular role in the disease establishment and progression. COPD is characterized by dysregulated immunity that has been associated with the bacterial colonization and infections. The establishment of culture-independent techniques has shed new light on the relationships between bacterial ecology and health status and expanded our knowledge on the lung microbiome. Interactions between the host and lung microbiome result in inflammation and activation of resident cells. The lung microbiome contains populations of symbionts and pathobionts in balance which lose their equilibrium and disturb the balance of T-helper and regulatory T-cells (Treg) upon infection, or lung disease. In COPD factors such as disease severity, exacerbations, degree of inflammation, and type of treatment used (e.g inhaled or systemic steroids and antibiotics) affect the composition of lung microbiota. Recent data indicate that the presence of specific bacterial taxa in the airways has the potential to influence the host immune response and possibly to interfere with disease phenotype. Although, there is a growing body of evidence for the role of microbiome in COPD several unanswered questions still exist for its clinical relevance. Highlights: The lung microbiome in chronic obstructive pulmonary disease (COPD) has a dynamic nature between stable state and exacerbation. Specific bacterial taxa in the airways may influence the host immune response and shape disease phenotypes and endotypes. However, the mechanisms by which microbiota regulate disease development and progression are not clear, as yet. The better understanding of these mechanisms could enable the development of novel treatments to improve the clinical outcomes in these patients